What's new in TensorFlow 2.0 : use the new and improved features of TensorFlow to enhance machine learning and deep learning /: use the new and improved features of TensorFlow to enhance machine learning and deep learning. (2019) - Baranwal, Ajay; Khatri, Alizishaan; Baranwal, Tanish
No abstract available